Remarks on the nomenclatural type of Cistus origanifolius Lamarck (Cistaceae) - Ferrer-Gallego, Pedro Pablo (Phytotaxa, 2015)
The genus Helianthemum Miller (1754: without page) (Cistaceae Jussieu [1789: 294]) is a monophyletic group limited to the Old World (Arrington & Kubitzki 2003, Guzmán & Vargas 2009, Sorrie 2011). It includes about 110 species and subspecies of small herbs or subshrubs, which are distributed from Macaronesia to C Asia, including Europe and North Africa, and mainly occurring in the W Mediterranean, particularly in the Iberian Peninsula (Greuter et al. 1984, López González 1993, Arrington & Kubitzki 2003, Parejo-Farnés et al. 2013).